(untitled) (International Journal of Automation and Smart Technology, 2015)
This paper presents a control framework for hierarchical coordination of multi-robot systems using leader-follower and region-based approaches. The leader robot is controlled to converge to and circulate along a closed curve that is defined by an implicit function. In the proposed control framework, only the leader robot has the knowledge of the desired curve, and the follower robots are controlled to track the curve indirectly through the leader robot. To enhance redundancy and flexibility of multi-robot systems, in practice the follower robots are controlled to stay freely within a designated region surrounding the leader robot. Moreover, the group of follower robots is able to circulate in the specified region to enlarge the sensing areas. The stability and convergence of the proposed multi-robot system with the addressed control algorithms are studied. Simulation and experimental results on mobile robots are presented to validate the performance of the hierarchical control framework for multi-robot systems.